The Academic Procrastination Behavior in Social Sciences Education Study Program Students, Tanjungpura University, Pontianak 2022/2023 - Sarah, Siti; Buwono, Sri; Karolina, Venny; Barella, Yusawinur; Wiyono, Hadi (Jurnal Ilmiah Wahana Pendidikan, 2024)
This study analyzes the causes of academic procrastination behavior in students of the social science education study program at Tanjungpura University pontianak in 2022/2023. The reason for this research is because the level of academic procrastination of students of the social science education study program at Tanjungpura University is high, the purpose of this study is to find out: the causes of students doing academic procrastination, the types of tasks that make academic procrastination, the losses obtained by students and the efforts made by students. The data collection technique is interview. The informants in this study were 5 people. Data were analyzed using thematic analysis. Suhadianto & Pratitis (2020) was used as a guide to categorize the interview results with the theme of academic procrastination. The results showed that the cause of students doing academic procrastination is that they consider the time for submitting assignments is still long. The results of this study are in accordance with the task collection data on the google classroom of the lecturer concerned that students are often late in submitting assignments that have been given